2023
DOI: 10.1111/joor.13466
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of Kovacs digital occlusal splint in the treatment of temporomandibular disorders: A single‐centre, cross‐sectional study

Abstract: Background: Digital occlusal splint is a novel approach in the treatment of temporomandibular disorders (TMD) and there is a lack of evaluation.Objective: To introduce Kovacs digital occlusal splint (KDOS) and evaluate its clinical and magnetic resonance imaging (MRI) outcomes and influencing factors in the treatment of TMD.Patients and Methods: Patients diagnosed of TMD by MRI and treated with KDOS from June 2020 to December 2021 were retrospectively reviewed. They were divided into three groups: anterior dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(55 reference statements)
2
3
0
Order By: Relevance
“…The second highest scoring domain was psychological disability (10.9 ± 2.8), which is supported by a bio-psychosocial model on TMD [ 29 ]. After KDOS treatment, the average physical pain score of the patients significantly reduced (10.2 ± 2.4, p < 0.001), and the improvement rate reached 69.8%, which was similar to the improvement rate (71.6%) in a previous KDOS study by Hua et al [ 13 ]. Consistent with their study, the pain improvement rate in the ADDwoR + OA group was the lowest among the three Wilkes stage groups, which may be related to greater tissue damage in the disease.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The second highest scoring domain was psychological disability (10.9 ± 2.8), which is supported by a bio-psychosocial model on TMD [ 29 ]. After KDOS treatment, the average physical pain score of the patients significantly reduced (10.2 ± 2.4, p < 0.001), and the improvement rate reached 69.8%, which was similar to the improvement rate (71.6%) in a previous KDOS study by Hua et al [ 13 ]. Consistent with their study, the pain improvement rate in the ADDwoR + OA group was the lowest among the three Wilkes stage groups, which may be related to greater tissue damage in the disease.…”
Section: Discussionsupporting
confidence: 86%
“…The binary logistic regression analysis revealed that patients with low QoL scores before treatment and those in the ADDwR and ADDwoR groups were likely to demonstrate a higher rate of improvement in the clinical symptoms following treatment with KDOS, which is similar to the results of Hua [ 13 ] and Clark et al [ 38 ] GHE et al [ 39 ] also reported that patients with joint pain or OA had lower QoL than those with myofascial pain or disc displacement. The present study concluded that the improvement rate of clinical symptoms was not associated with the age and sex of the patients; moreover, Emshoff et al [ 40 ] did not find any influence of age on the prognosis of stabilization occlusal splint treatment; however, Hua et al [ 13 ] demonstrated that the older the patient, the higher the possibility of improvement, which may be attributed to the difference in sample size and population characteristics.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Occlusion is often considered a major cause of TMD. Numerous etiological and therapeutic theories are based on this presumed association and have been applied to justify the use of several therapeutic approaches, such as occlusal splint [ 3 ]. Conversely, many TMD experts hold opposing views, and various kinds of dental interventions, including routine orthodontic treatment, have been reported as causes of TMD [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%